Application of Restorative Justice In The Settlement of Customary Criminal Cases - Salamor, Anna Maria; Titahelu, Juanrico Alfaromona Sumarezs; Ubwarin, Erwin; Taufik, Iqbal (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Indonesia is a country with a variety of ethnic and cultural patterns, including race, language, and others. With diversity in each customary area, it has different rules and legal regulation because it has its own customs.Purposes of the Research: The purpose of this research is to find out the application of restoration justice in the settlement of customary criminal casesMethods of the Research: Normative legal research is carried out by examining laws and regulations, jurisprudence and values that lives in societyResults of the Research: The application of restorative justice as long as it does not conflict with positive law or customary law can be used in resolving customary criminal cases that occur as in Nua Nea Country and Akoon Country while upholding the customary values of their respective regions. the application of customary criminal punishment can provide a deterrent effect for perpetrators who make mistakes and do not repeat their actions again.